The Effects Of Digital Financial Literacy, Online Shopping Frequency, And Financial Self-Control on Financial Management, With Lifestyle as a Moderating Variable - Firli Cantika Khaerunisa; Dien Noviany Rahmatika; Aminul Fajri (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to examine the influence of Digital Financial Literacy, Online Shopping Frequency, and Self-Control Financial on Financial Management, with Lifestyle as a moderating variable among Accounting students in Tegal City. The study is motivated by the rapid development of digital technology, which has facilitated access to digital financial services while simultaneously increasing students' online shopping activities. These conditions require students to possess adequate digital financial literacy and self-control to manage their personal finances effectively. In addition, lifestyle is assumed to strengthen or weaken the relationship between these factors and financial management.This research employed a quantitative approach using primary data collected through questionnaires distributed to 315 Accounting students in Tegal City. The sampling technique used simple random sampling. Data were analyzed using SPSS through descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, Moderated Regression Analysis (MRA), t-test, F-test, and the coefficient of determination (R²).The results indicate that Digital Financial Literacy, Online Shopping Frequency, and Self-Control Financial each have a positive and significant effect on Financial Management. The moderation analysis reveals that Lifestyle moderates the relationship between In conclusion, higher digital financial literacy, controlled online shopping frequency, and stronger financial self-control contribute to better financial management among students. Furthermore, lifestyle plays an important role in influencing the effectiveness of digital financial literacy and self-control in shaping financial management behavior, while it does not moderate the relationship between online shopping frequency and financial management.